Which cyclists manage to cope with the corona crisis in a resilient way? The role of motivational profiles - Morbée, S.; Haerens, L.; Waterschoot, J.; Vansteenkist, M. (International Journal of Sport and Exercise Psychology, 2022)
Due to the COVID-19-pandemic, all cycling races during spring 2020 were cancelled, thus requiring cyclists to act in resilient ways. This cross-sectional study examined in a sample of 207 cyclists (Mage = 26.81) whether different motivational profiles can be identified and whether these profile differences relate to (a) the extent to which cyclists get their basic psychological needs satisfied during this pandemic and (b) the type of self-regulation strategies cyclists use to motivate themselves to continue their training. Cluster analyses revealed four motivational profiles (i.e., a good quality, high quantity, low quantity, and poor quality profile) that differed in terms of autonomous motivation, controlled motivation, and amotivation. Results indicated that the profile characterised by autonomous motivation (i.e., good quality) yielded the most adaptive outcomes, while the profile characterised by the combination of controlled motivation and amotivation (i.e., poor quality) yielded the least optimal outcomes. This research shows that cyclists` capacity to cope with the pandemic in a resilient way depends on the presence of both a sufficient dose and high-quality motivation.